Current Status and Prospects of Occupational Medicine in the Russian Federation - Nailya N. Mazitova; Nadejda I. Simonova; Lynn C. Onyebeke; Andrey V. Moskvichev; Elena E. Adeninskaya; Andrey S. Kretov; Marina V. Trofimova; Minzilya M. Sabitova; Andrey Yu Bushmanov (Ubiquity Press, 2015)
An in-depth analysis conducted on the historical background and current status of occupational medicine in Russia is presented. Scientific and practical bases of occupational medicine in the Russian Federation were based on 2 of the most important principles of health service: free medical care and its preventive orientation. Our analysis of the current situation in occupational medicine in modern Russia shows a transition from the vision of zero occupation-related harm to the strategy of recognizing, assessing, and managing occupational exposures. The system of workplace monitoring is developing successfully, with the creation of a federal database for the state of working conditions and the implementation of mechanisms for occupational risk assessment and management. However, at the same time, the system of medical surveillance for workers needs substantial reform. Over the past few years, the professional community of specialists in occupational medicine has taken several steps to improve the quality of its work. Understanding of the need for reforming the system of occupational medicine has continued to grow, which will improve the quality of medical monitoring for workers and extend professional longevity. Current challenges and prospects of occupational medicine in the Russian Federation are discussed.